Synthesis of Nanofiltration Membrane Developed from Triethanolamine (TEOA) and Trimesoyl Chloride (TMC) for Separation of Xylose from Glucose - Nurul Fatihah, Mahamad Roli; Wan Mohd Hafizuddin, Wan Yussof; Syed Mohd Saufi, Tuan Chik; Mazrul Nizam, Abu Seman; Abdul W., Mohammad (AIDIC Servizi, 2017)
Synthesis of thin film composite (TFC) nanofilt ration (NF) membrane has experienced tremendous development since the concept of interfacial polymerisation (IP) was first introduced. One of its new application is on the separation of xylose from glucos e in biomass hydrolysate. In this present study, NF TFC membrane has been produced through interfacial poly merisation by manipulation the concentration of triethanolamine (TEOA) at 35 min reaction time with 0. 15 % w/v of trimesoyl chloride (TMC). The membrane was then characterised in term of their chemical and physical properties, and separation performance between xylose and glucose. The growth of thin layer f ilm depends on concentration of TEOA as the monomer and reaction time. As concentration of TEOA and re action time increased, the layer of the TFC becomes thicker thus decreases the permeability of the membrane. Contradicted to this study, the lowest and the highest permeability were recorded at 4 % w/v of TEOA and 8 % w/v of TEOA at reaction time of 35-min in TMC. The TFC membrane prepared with 4 % w/v TEOA has high in permeate flux, resultant in high xylose separation of 1.3. Low permeate flux but moderate xylose separation factor of 0.93 was obtained for the TFC membrane prepared with 8 % w/v TEOA.